Komisaris Independen sebagai Variabel Moderasi antara Pengaruh Intensitas Modal, Intensitas Persediaan dan Ukuran Perusahaan terhadap ETR (Effective Tax Rate) - Arnoni Hafsari Wastiti; Saiful Anwar (Journal of Management and Bussines (JOMB), 2023)
This research aims to analyze the influence of capital intensity, inventory intensity, and company size on the moderating effect of independent commissioners in influencing tax aggressiveness, which is the aim of this research. Quantitative research was used in this research. This research produces the implication that the tax aggressiveness carried out by companies in the 2018-2021 period is the result of increasing capital intensity and organizational size. This research is largely based on agency theory, where the fundamental desire of the principal (owner) is to comply with existing tax standards, but the agent (management) emphasizes obtaining excessive income, therefore agents use various strategies to reduce the company's tax burden. Keywords: Tax Aggressiveness, Independent Commissioner, Capital Intensity